Effects of montelukast on the healing of ischemic colon anastomoses - (:unkn) unknown (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2013)
BACKGROUND: The aim of this study was to examine whether treatment with montelukast, a selective leukotriene antagonist, would affect anastomotic healing in a reperfused colon rat model with remote ischemia/reperfusion injury. METHODS: Rats (n = 12 per group) were intraperitoneally administered normal saline or 10 mg/kg montelukast sodium 60 minutes before and for 5 days after surgery. Ischemia was induced for 45 minutes through superior mesenteric artery occlusion. A left colon anastomosis was made. Blood and peri-anastomotic tissue samples were obtained on postoperative day 5. RESULTS: Mean anastomotic bursting pressures of the control and montelukast groups were 159.17 +/- 29.99 and 216.67 +/- 26.40, respectively (P < .001). Compared with saline, montelukast treatment increased the mean tissue hydroxyproline level (2.46 +/- .30 vs 3.61 +/- .33 mu mol/L) and decreased tissue caspase-3 activity (36.06 +/- 5.72 vs 21.78 +/- 3.87) and malondialdehyde levels (3.43 +/- .34 vs 2.29 +/- .34 nmol/g) (P < .001 for all). Other plasma markers of injury also showed differences. CONCLUSIONS: Montelukast prevented ischemia/reperfusion-induced damage in a rat model of colonic anastomotic wound healing. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Ischemia/reperfusion; Colon anastomoses; Montelukast; HEPATIC ISCHEMIA/REPERFUSION INJURY; RECEPTOR BLOCKER MONTELUKAST; INFLAMMATORY-BOWEL-DISEASE; REPERFUSION INJURY; INTRAABDOMINAL SEPSIS; RATS; INHIBITION; ANTAGONIST; PROTECTS; SURVIVAL